Characterising the Blood Pressure Response to Physical Counterpressure Manoeuvres Using Surface Electromyography in Adults with Long Covid - Romero-Ortuno, Roman (My University, 2023)
Objective: Orthostatic intolerance (OI) is common in Long Covid. Physical counterpressure manoeuvres (PCM) may improve OI in other disorders. We characterised the blood pressure-rising effect of PCM using surface electromyography (sEMG) and investigated its association with fatigue in adults with Long Covid. Methods: Participants performed an active stand with beat-to-beat hemodynamic monitoring and sEMG of both thighs, including PCM at 3-minutes post-stand. Multivariable linear regression investigated the association between change in systolic blood pressure (SBP) and change in normalised root mean square (RMS) of sEMG amplitude, controlling for confounders including the Chalder Fatigue Scale (CFQ). Results: In 90 participants (mean age 46), mean SBP rise with PCM was 13.7 (SD 9.0) mmHg. In regression, SBP change was significantly, directly associated with change in RMS sEMG (β=0.25, 95% CI 0.07–0.43, P=0.007); however, CFQ was not significant. Discussion/Conclusion: PCM measured by sEMG augmented SBP without the influence of fatigue.
PUBLISHED
Keywords: COVID-19; Muscles; Fatigue; Phase change materials; Blood pressure; Biomedical monitoring; Ageing; Immunology, Inflammation & Infection; Neuroscience; Next Generation Medical Devices; Smart & Sustainable Planet; COVID 19; Chronic Health Condition; Mental Health/Psychosocial disability; Health; Third age/ageing